‘A queer combination of a child’s mind with a grown-up joke’: Dickens’s Child Narrators in Holiday Romance (1868) - Isabelle Hervouet (Cahiers Victoriens et Edouardiens)
Holiday Romance, written by Dickens and first published in 1868, is a collection of four tales for children in which Dickens indulges his penchant for fairy tales, child-like vision and verbal play. It features four child narrators embarked on a mission: adults are at so great a remove from childhood that they are unable to see the importance of imagination and of story-telling; the four children will have to reinvent the world and tell adults what it should be like. The collection therefore presents distinct parallels with ‘Fraud on the Fairies’ (Household Words, 1853), in which Dickens speaks out against a tendency to deprive children of the type of literature that should feed their imagination for the rest of their lives. The originality, appeal and ambivalence of the collection thus originate in the use of child narrators and in their avowed desire to teach adults a lesson, while also addressing child-readers, therefore teaching adults-in-the-making. Dickens wished Holiday Romance would mould (to a certain extent) the attitudes of his child readers. This paper thus attempts to determine how he talks to children in Holiday Romance, i.e. both how the stories’ implied child readers are addressed by author and narrators, and what Dickens’s treatment of his child narrators is. It aims to show that Dickens throughout adopts an empathetic representation of a child’s point of view and addresses his child readers with the utmost respect.